Life After Residency A Career Planning Guide - Berhow, Melissa T.; Feaster, William W.; Brock-Utne, MD, PhD, FFA(SA), John G. (Springer New York : Imprint: Springer, 2009)
Life After Residency: A Career Planning Guide is an insightful, step-by-step guide to achieving a successful and fulfilling career in medicine. As professors at Stanford University Medical Center, Drs. Melissa Berhow, William Feaster, and John Brock-Utne began running seminars to advise their residents not only on creating a curriculum vitae and landing a great job, but also on how to manage student loan payments and avoid pitfalls in the life of a physician. The immense success and ensuing demand for more seminars eventually gave rise to Life After Residency-a book which continues the seminar discussions in greater depth and magnitude, while maintaining a conversational writing style. Other key topics covered include: Preparing for a job interview Evaluating job offers and negotiating contracts Obtaining and maintaining the proper State license How to apply for membership onto Medical Staffs Obtaining malpractice insurance Buying a house and investing for eventual retirement Advice for non-medical career options Loaded with sage advice and practical wisdom, Life After Residency is an invaluable asset to every resident during the transition from residency to life thereafter.